Pengaruh Program Edukası Hıdup Sehat terhadap Penurunan Berat Badan dan Lıngkar Perut pada Mahasıswa Keperawatan - Haris Haris (Journal Borneo, 2023)
Obesity and abdomen circumference are risk factors for non-communicable diseases. These signs are commonly seen in productive age groups, specifically students. A healthy way of life is essential for avoiding extra weight and abdominal girth. The purpose of this study is to examine the impact of healthy living on weight loss and abdominal circumference. A quasi-experiment with no control was used as the study approach. Body weight and abdomen circumference are the dependent variables, and health education is the independent variable. The target population comprises 93 students enrolled in the D3 Nursing study program. Purposive sampling was utilized in this study. Students are the inclusion criteria. Students who have a weight above their normal using an ideal body weight indicator and are willing to participate in the program for 7 days complete the inclusion requirements. While the exclusive criteria are students with a history of hypertension or diabetes mellitus, they also include students who feel ill when their weight and abdomen circumference are measured. There were 28 people who responded. Respondents reflect on their healthy lifestyle activities for seven days. Following the pre-test and post-test, the two data sets were processed and the data normality test was performed, yielding normal distribution data. A paired t-test was performed as a result of this. Results. The difference in weight before and after the education program had a p-value of 0.000, whereas the difference in abdominal circumference had a pvalue of 0.000. Limiting the amount of high carbohydrates and fats in diet as well as doing physical activity can reduce body fat formation and thus have an impact on weight loss. Conclusion. The healthy living program influences body weight and abdomen level